2018
DOI: 10.1002/eat.22851
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adverse life events, disordered eating, and body mass index in US Military service members

Abstract: Findings support evaluating childhood ALE exposure among service members with disordered eating and weight concerns. Moreover, findings support the need for prospective research to elucidate these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…The findings in this review support the extensive literature on the relationship of adverse childhood experiences and MST with EDs and DE in addition to other traumas such as verbal abuse and weight harassment (Arditte Hall et al, 2018; Bakalar et al, 2018; Blais et al, 2017; Breland, Donalson, Li, et al, 2018; Cuthbert et al, 2020; Donaldson, 2016; Forman‐Hoffman et al, 2012; Guillaume et al, 2016; Hasan et al, 2019; McNulty, 2001; Warner et al, 2007). Other forms of trauma more specific to the military that were related included the loss of fellow servicemembers, acting against one's morals, and enduring IPV (Arditte Hall et al, 2017; Bartlett et al, 2018; Creech et al, 2021; Huston et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings in this review support the extensive literature on the relationship of adverse childhood experiences and MST with EDs and DE in addition to other traumas such as verbal abuse and weight harassment (Arditte Hall et al, 2018; Bakalar et al, 2018; Blais et al, 2017; Breland, Donalson, Li, et al, 2018; Cuthbert et al, 2020; Donaldson, 2016; Forman‐Hoffman et al, 2012; Guillaume et al, 2016; Hasan et al, 2019; McNulty, 2001; Warner et al, 2007). Other forms of trauma more specific to the military that were related included the loss of fellow servicemembers, acting against one's morals, and enduring IPV (Arditte Hall et al, 2017; Bartlett et al, 2018; Creech et al, 2021; Huston et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Deployment, in general, was not related to new ED onset (Jacobson et al, 2009). Adverse life events, including childhood trauma, adult sexual assault, and verbal abuse, were associated with DE, as was military sexual trauma (MST; Arditte Hall et al, 2018; Bakalar et al, 2018; Berg & Moore, 1996; Blais et al, 2017; Breland, Donalson, Li, et al, 2018; Donaldson, 2016; Forman‐Hoffman et al, 2012; Warner et al, 2007). Qualitative research on female veterans found that DE can be related to trauma and used to prevent unwanted attention and cope short‐term (Breland, Donalson, Li, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The mean ± SD and median±interquartile range (IQR) LSC-R scores were 9.6±11 and 6.0±8.0, respectively, and the range was 0–96. These scores are higher than those reported by a sample of 179 active-duty U.S. military service members (4.5±5.7, range: 0–35) (Bakalar et al. 2018), but lower than a clinical sample of new mothers enrolled in substance-abuse treatment program (n=21, 45.1±24.4, range: 17–104) and their demographically matched controls (n=27, 19.6±11.2, range: 2–58) (Goldman Fraser et al.…”
Section: Resultscontrasting
confidence: 62%
“…Another important factor which seems to support the assumption that men who work in dangerous professions are likely to employ fast LH strategies is the high morbidity-mortality rate among soldiers and firefighters. Specifically, soldiers are found to be at increased risk of developing depression, posttraumatic stress disorder (PTSD; Grieger et al 2006 ; Hoge et al 2008 ), and obesity (Bakalar et al 2018 ), which can noticeably and negatively affect life expectancy and quality of life in general. In the context of more proximate risk factors, military physical training causes a larger number of injuries (Smith and Cashman 2002 ), to say nothing of dangerous combat exposure (Grieger et al 2006 ; Hoge et al 2008 ).…”
Section: Life History Theorymentioning
confidence: 99%